O33 Outcomes of patients undergoing emergency surgery during the first phase of national lockdown in the United Kingdom due to COVID-19 pandemic: experience at a district general hospital. (30th July 2021) - Luo, W; Limb, R; Aslam, A; Kattimani, R; Karthikappallil, D; Paramasivan, A; Waseem, M
Abstract: Introduction: This study aimed to assess the impact of the COVID-19 pandemic on emergency operations during the first phase of lockdown in the United Kingdom, compared to the equivalent population in the same calendar period in 2019. Method: We retrospectively reviewed patients undergoing surgery in emergency theatres at our district general hospital between March 23 rd and May 11 th in 2019 and 2020. Data collected included demographics, National Confidential Enquiry into Patient Outcome and Death (NCEPOD) category and procedure. The primary outcome was 90-day post-operative mortality; secondary outcomes included time to intervention and length of inpatient stay. Result: 132 patients (2020) versus 141 (2019) patients were included with no significant difference in age ( P = 0.676), sex ( P = 0.230), or overall 90-day postoperative mortality ( P = 0.196). Notably, time to intervention was faster for NCEPOD code 3 patients in 2020 than 2019 ( P = 0.027). Time to intervention in 2020 was longer for those dying within 90 days post-operatively compared to survivors ( P = 0.02). There was no difference in length of stay between years, both overall and when comparing subgroups by NCEPOD category or procedures (fractured neck of femur ( P = 0.776), laparoscopies ( P = 0.866), laparotomies ( P = 0.252)), except for upper limb trauma ( P = 0.007). Conclusion: This study is amongst the first describing the general case mix in emergency theatres in the UK. Patient pre-operative characteristics and demographics did not change. Our data confirms patient prioritisation according to NCEPOD recommendations and streamlining of surgical services, with no difference in overall mortality, time to intervention or length of stay compared to 2019. Take-home Message: At this district general hospital, patients were appropriately prioritised, and our results show adaptation of hospital practice to emerging national guidelines during the first phase of lockdown. A national validation audit assessing morbidity and mortality outcomes for all NCEPOD patients may be facilitate further understanding of risks posed to patients requiring urgent surgery during these unprecedented times.